2006
DOI: 10.1086/504966
|View full text |Cite
|
Sign up to set email alerts
|

The End of the Reionization Epoch Probed by Lyα Emitters atz= 6.5 in the Subaru Deep Field

Abstract: We report an extensive search for Ly emitters (LAEs) at z ¼ 6:5 in the Subaru Deep Field. Subsequent spectroscopy with Subaru and Keck identified eight more LAEs, giving a total of 17 spectroscopically confirmed LAEs at z ¼ 6:5. Based on this spectroscopic sample of 17, complemented by a photometric sample of 58 LAEs, we have derived a more accurate Ly luminosity function of LAEs at z ¼ 6:5, which reveals an apparent deficit at the bright end of $0.75 mag fainter L Ã , compared with that observed at z ¼ 5:7. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
716
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 425 publications
(764 citation statements)
references
References 79 publications
(144 reference statements)
37
716
11
Order By: Relevance
“…The acquisition and reduction of these data have been discussed extensively in Kashikawa et al (2004Kashikawa et al ( , 2006, Ly et al (2007;hereafter Ly07), as well as in Ly et al (2012b) for the narrowband data, and in Nagao et al (2008) for the intermediate-band data. In brief, data were obtained mostly under photometric conditions with average seeing of 0 9-1 0 for all five narrowband and two intermediate-band filters.…”
Section: The Subaru Deep Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquisition and reduction of these data have been discussed extensively in Kashikawa et al (2004Kashikawa et al ( , 2006, Ly et al (2007;hereafter Ly07), as well as in Ly et al (2012b) for the narrowband data, and in Nagao et al (2008) for the intermediate-band data. In brief, data were obtained mostly under photometric conditions with average seeing of 0 9-1 0 for all five narrowband and two intermediate-band filters.…”
Section: The Subaru Deep Fieldmentioning
confidence: 99%
“…The distribution of onsource integration times is illustrated in Figure 5. Kashikawa et al (2006) and Ly07, and the 2008-2009 data have been discussed in Kashikawa et al (2011). In brief, we constructed 22 slitmasks with 1″ slit widths, and used the 830 line mm −1 grating and GG495 order-cut filter.…”
Section: Mmt/hectospec Observing Programmentioning
confidence: 99%
“…For the χ HI value shown in Column 1, we summarise the fα/fc ratio required to best fit the simulated Lyα LF to observations (Kashikawa et al 2011) within 1σ limits in columns 2-4 with subscripts showing the fesc value used (Hutter et al 2014 to narrow the joint constraints on χHI , fesc and fα/fc. We start by describing our procedure for obtaining LAE ACFs, which depends both on the depth along the LOS (Peebles 1980) since all galaxies are projected to a plane perpendicular to the LOS, as well as the chosen field of view (FoV), which should be comparable to that observed (Kashikawa et al 2006). Indeed, while the measured ACF should be independent of the FoV if large enough areas are sampled, the restricted observational FoV leads to an ACF that is not independent of sample variance.…”
Section: Constraints From Lae Clusteringmentioning
confidence: 99%
“…As seen from this equation, even a neutral hydrogen fraction as low as 10 −5 can lead to a significant attenuation of Lyα photons at high-z , making them extremely sensitive probes of H I in the IGM. As a result, a class of high-z galaxies called Lyman Alpha Emitters (LAEs), detected by means of their Lyα line (at 1216Å in the rest frame), have become popular probes of reionization, with statistically significant samples available in the reionization epoch, at z 5.7 and 6.6 (Malhotra et al 2005;Taniguchi et al 2005;Shimasaku et al 2006;Hu et al 2010;Kashikawa et al 2006;Ouchi et al 2010;Kashikawa et al 2011). Indeed, a number of theoretical papers have used semi-analytic (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1 (right) show that these limits are already close to the maximum or slightly below the predicted values for metal-free populations with IMFs including very massive stars. Kashikawa et al (2006), andOta et al (2008) at z = 5.7, 6.5, and 7, as well as the z ∼ 8.5 to 10 lensed candidates of Stark et al (2007) are shown by the filled circles (observed fluxes, and crosses: intrinsic fluxes for lensed objects). The black line shows the flux limit from deep NIRSPEC/Keck spectroscopy of Richard et al (2008) from 0.95 to 1.1 μm.…”
Section: Upper Limits From Individual Objects or Composite Spectramentioning
confidence: 99%